Consciousness embodied: language and the imagination in the communal world of William Blake - Pierce, Robyn (My University, 2014)
This dissertation examines the philosophical and spiritual beliefs that underpin William Blake’s account of the imagination, his objections to empiricism and his understanding of poetic language. It begins by considering these beliefs in relation to the idealist principles of George Berkeley as a means of illustrating Blake’s own objections to the empiricism of John Locke. The philosophies of Locke and Berkeley were popular in Blake’s society and their philosophical positions were well known to him. Blake and Berkeley are aligned against Locke’s belief in an objective world composed of matter, and his theory of abstract ideas. Both reject Locke’s principles by affirming the primacy of the perceiving subject. However, Blake disagrees with Berkeley’s theologically traditional understanding of God. He views perception as an act of artistic creation and believes that spiritual divinity is contained within and is intrinsic to man’s human form. This account of human perception as the creative act of an immanent divinity is further elucidated through a comparison with the twentieth-century existential phenomenology of Maurice Merleau-Ponty. In the Phenomenology of Perception (1945), Merleau-Ponty examines human experience as the functioning of an embodied consciousness in a shared life-world. While Merleau-Ponty does not make any reference to a spiritual deity, his understanding of experience offers a link between Berkeley’s criticisms of Locke and Blake’s own objections to empiricism. Through a comparative examination of Blake and Merleau-Ponty, the imagination is revealed to be the creative or formative consciousness that proceeds from the integrated mind-body complex of the “Divine Body” or “human form divine”. This embodied existence locates the perceiving self in a dynamic physical landscape that is shared with other embodied consciousnesses. It is this communal or intersubjective interaction between self and other that constitutes the experienced world. Merleau-Ponty’s account of the chiasm and his notion of flesh, discussed in The Visible and the Invisible, are applied to Blake in order to elucidate his belief in poetic vision and the constitutive power of language. The form and function of language are compared with that of the body, because both bring the individual experience of a perceiving subject into being in the world and facilitate the reciprocal exchange between the self and other. Ultimately, this dissertation argues that Blake characterises the body and language as the living media of the imagination, which facilitate a creative exchange between a perceiving self and a shared life-world.
Keywords: Willian Blake; imagination; language; community; John Locke; empiricism; George Berkeley; idealism; Maurice Merleau-Ponty; phenomenology; embodied consciousness; chiasm; Blake, William,1757-1827--Criticism and interpretation